Retrospective Analysis of Leprosy cases at Mayo Hospital Lahore: Demographic Trends and Clinical Profiles (Journal of Fatima Jinnah Medical University, 2026)
Background: Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae. This debilitating disease mainly affects the skin, peripheral nerves, and eyes, which may lead to progressive damage if left untreated. We conducted this study to analyze the demographic trends and clinical profiles of leprosy patients registered at Mayo Hospital, Lahore.Methods: A retrospective, observational study was conducted utilizing available medical records of all new leprosy cases diagnosed and registered in the leprosy clinic of the Dermatology Department, Mayo Hospital, over a five-year period. Data on demographic details (age, gender) and clinical presentations were collected and analyzed.Results: From January 2019 to December 2023, a total of 122 new cases of leprosy were registered at Mayo Hospital’s Leprosy Department, showing a decreasing trend over the years. Among these, 64 (52.5%) were male, and 58 (47.5%) were female. Three patients (2.5%) were children (
Keywords: Leprosy; Multibacillary; Paucibacillary